A Contextual Digital Learning Model: Integrating CSCL and Project-Based Learning in E-Learning for CAD Education - Muvi Yandra; Rahmi Oktarina (International Journal of Multidisciplinary Research of Higher Education, 2026)
This study aims to develop a Computer-Supported Collaborative Learning based instructional design through the integration of an e-learning platform in the Computer Aided Design (CAD) course at Universitas Negeri Padang, employing a Project-Based Learning approach and social constructivism. The study adopts the ADDIE development model, which consists of analysis, design, development, implementation, and evaluation stages. The results of expert validation, involving both content and media experts, indicate that the developed instructional materials are categorized as highly feasible. The implementation was conducted using a blended learning scheme and demonstrated significant improvements across multiple learning outcomes. Students’ conceptual understanding increased, engagement improved, and learning satisfaction rose. In addition, students’ learning motivation showed a consistent overall improvement. These findings suggest that the developed Computer-Supported Collaborative Learning-based instructional design is not only technically effective but also enhances collaborative interaction, fosters critical thinking skills, and prepares students to meet industry demands. This study contributes to the advancement of contextual digital learning models in engineering education and recommends the integration of learning analytics to support continuous evaluation and improvement.